2020
DOI: 10.1162/netn_a_00148
|View full text |Cite
|
Sign up to set email alerts
|

Test-retest reliability of the human functional connectome over consecutive days: identifying highly reliable portions and assessing the impact of methodological choices

Abstract: Countless studies have advanced our understanding of the human brain and its organization by using functional magnetic resonance imaging (fMRI) to derive network representations of human brain function. However, we do not know to what extent these “functional connectomes” are reliable over time. In a large public sample of healthy participants ( N = 833) scanned on two consecutive days, we assessed the test-retest reliability of fMRI functional connectivity and the consequences on reliability of three common s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
50
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(52 citation statements)
references
References 56 publications
2
50
0
Order By: Relevance
“…Even if the absolute changes in brain network metrics are very small, functional connectomes rely on functional and structural connections (Shen et al 2015 ). Therefore, intra-individual modulations brain graphs should not be expected to be drastic within a given session as structural connections do not change extensively within short time periods (Tozzi et al 2020 ). Traditionally, theta oscillations are suggested to originate from the prefrontal cortex and reflect attentional involvement and executive function (Sauseng et al 2005 ).…”
Section: Discussionmentioning
confidence: 99%
“…Even if the absolute changes in brain network metrics are very small, functional connectomes rely on functional and structural connections (Shen et al 2015 ). Therefore, intra-individual modulations brain graphs should not be expected to be drastic within a given session as structural connections do not change extensively within short time periods (Tozzi et al 2020 ). Traditionally, theta oscillations are suggested to originate from the prefrontal cortex and reflect attentional involvement and executive function (Sauseng et al 2005 ).…”
Section: Discussionmentioning
confidence: 99%
“…As a brain graph is a result of both functional and structural connections which contribute to an existing connectome, both chronic and acute neuroplastic changes contribute to modulations of brain graphs. While structural connections are expected to remain stable over time, specific functional connections are more likely to rather reflect state than trait and therefore fluctuate more within smaller time periods 40 , 41 . Even if the analysis of brain graphs is majorly applied to distinguish healthy from diseased populations exposed to long-term neuroplastic changes 42 , first studies have shown that even acute circumstances like fatigue or vigilance correlate with modulations of functional graph outcomes 43 , 44 .…”
Section: Discussionmentioning
confidence: 99%
“…We showed that structural brain measures generally showed poorer replicability than functional brain measures. Paradoxically, test-retest reliability for functional MRI is lower than for structural MRI [44][45][46] . This indicates that the additional noise from lower test-retest reliability of functional MRI is less important than the higher association strength for the replication of brainphenotype associations.…”
Section: Discussionmentioning
confidence: 97%